Impact of seasons and heat waves on the incidence of Staphylococcus aureus and Escherichia coli bacteremia – A prospective multicenter study using biometeorological data - Philipp Mathé; Kathrin Graw; Andreas Matzarakis; Máté Elod Maros; David Tobys; Britta Kohlmorgen; Nadja Käding; Silke Peter; Harald Seifert; Petra Gastmeier; Jan Rupp; Siri Göpel; et al. (PLoS ONE, 2026)
Objectives Climate change and global warming are major threats for human health and impact the burden of infectious diseases. We investigated the effect of heat stress days (max. perceived temperature ≥32°C) on the incidence of Staphylococcus aureus bacteremia (SAB) and Escherichia coli bacteremia (ECB). Methods We performed a post-hoc analysis of a prospective multicenter cohort study with inclusion of all reported SAB and ECB episodes at six tertiary care centers in Germany from 01/2017–12/2019. The effect of the number of heat stress days on the incidence of bacteremia episodes was modelled by a negative binomial regression model with and without underlying seasonal trend. Results In the prospective multicenter cohort, we included 2870 episodes of SAB and 4421 episodes of ECB. For both entities, we found a significant seasonal variation over the year (ECB peak-to-trough ratio: 1.33, 95% CI: 1.23–1.45, p < 0.001); SAB peak-to-trough ratio: 1.19 (95% CI: 1.07–1.32, p < 0.001), especially in the subgroup of community-acquired ECB (1.47, 95%-CI: 1.32–1.64, p < 0.001). In the model with incorporation of an underlying seasonal trend, we discovered no overall significant association with the number of heat stress days for SAB and ECB. However, in the subgroup of patients with hospital-acquired SAB, we found a significant association after two days of heat (IRR 1.45, 95%-CI: 1.17–1.82, p = 0.001), that remained significant also in a sensitivity analysis focusing on summer days only (IRR 1.50, 95%-CI: 1.18–1.91, p = 0.001). However, after inclusion of an underlying seasonal trend, the incidence of bacteremia cases remained significantly associated with heat stress days only in the subgroup of patients with hospital-acquired SAB. Conclusion Apart from seasonal trends, heat days did not seem to influence the incidence of SAB and ECB overall. The observed association of SAB with heat days in the subgroup of hospital-acquired SAB needs confirmation in further studies.